Comparison of imaging methods in POEMS syndrome - Minarik, Jiri; Scudla, Vlastimil; Bacovsky, Jaroslav; Pika, Tomas; Ctvrtlik, Filip; Metelkova, Iva; Myslivecek, Miroslav (Biomedical papers, 2012)
Background: POEMS syndrome is a clinical condition with a very heterogeneous clinical manifestation. Its presentation as well as monitoring is complex and dependent on the clinician's experience. One of the leading presenting symptoms is based on evaluation of skeletal damage with typical osteosclerotic or mixed lesions.Aims and methods: Our aim was to compare the usefulness of different imaging methods in the diagnostics of POEMS syndrome, such as conventional radiography, densitometry, technetium scintigraphy, PET/CT scan, MRI and angiography on a series of three patients with POEMS syndrome with different clinical manifestations and course of disease.Results: Our series demonstrates different types of skeletal involvement in POEMS syndrome. Although conventional X-ray is the imaging method mostly used for the evaluation, its sensitivity and specificity is low. Under specific conditions, other imaging methods should be considered, giving a more complex outlook of the disease's skeletal involvement. Nevertheless, FDG-PET/CT confirmed its superiority in defining both skeletal lesions as well as the activity of the neoplastic process.Conclusions: We conclude that the different manifestation of the disease implies the necessity of a complex evaluation of imaging methods in mutual concordance. FDG-PET/CT emerges as the most contributive method for the evaluation of both the extent and activity of the disease.
Keywords: POEMS syndrome; imaging; PET/CT; conventional radiography; computed tomography; magnetic resonance